A practical guide to Ubuntu Linux - Sobell, Mark G. (Prentice Hall, 2008)
A new edition of this title is available, ISBN-10: 0137003889 ISBN-13: 9780137003884 Praise for A Practical Guide to Ubuntu Linux® "I am so impressed by how Mark Sobell can approach a complex topic in such an understandable manner. His command examples are especially useful in providing a novice (or even advanced) administrator with a cookbook on how to accomplish real-world tasks on Linux. He is truly an inspired technical writer!"--George Vish II, Senior Education Consultant, Hewlett-Packard Company "Overall, I think it's a great, comprehensive Ubuntu book that'll be a valuable resource for people of all technical levels." -John Dong, Ubuntu Forum Council Member, Backports Team Leader "The JumpStart sections really offer a quick way to get things up and running, allowing you to dig into the details of his books later." -Scott Mann, Aztek Networks "Ubuntu is gaining popularity at the rate alcohol did during prohibition, and it's great to see a well-known author write a book on the latest and greatest version. Not only does it contain Ubuntu-specific information, but it also touches on general computer-related topics, which will help the average computer user to better understand what's going on in the background. Great work, Mark!" -Daniel R. Arfsten, Pro/ENGINEER Drafter/Designer "I read a lot of Linux technical information every day, but I'm rarely impressed by tech books. I usually prefer online information sources instead. Mark Sobell's books are a notable exception. They're clearly written, technically accurate, comprehensive-and actually enjoyable to read." -Matthew Miller, Senior Systems Analyst/Administrator, BU Linux Project, Boston University Office, of Information Technology "I would so love to be able to use this book to teach a class about not just Ubuntu or Linux but about computers in general. It is thorough and well written with good illustrations that explain important concepts for computer usage." -Nathan Eckenrode, New York Local Community Team Praise for Other Books by Mark Sobell "I currently own one of your books, A Practical Guide to Linux ® . I believe this book is one of the most comprehensive and, as the title says, practical guides to Linux I have ever read. I consider myself a novice and I come back to this book over and over again." -Albert J. Nguyen "Thank you for writing a book to help me get away from Windows XP and to never touch Windows Vista. The book is great; I am learning a lot of new concepts and command ...